Personal Data Security in Comparative Perspective: Legal Frameworks and Protections - Zarkua, Mariam (European Scientific Journal, ESJ, 2026)
The paper presents the general concept of personal data protection, its legal approaches in the European Union, the United States, Japan and Georgia and its main purpose is to study different legal frameworks and approaches that underlie the formation and development of general data protection policies. The present study examines the primary legislative instruments, including the GDPR and the CCPA, which are discussed below, as well as Japanese and Georgian legal regulations. The study’s objective is to assess the legal standards of these states with a particular focus on the extent to which they balance and protect the confidentiality of individuals’ personal data, while considering commercial interests and state needs. The study utilizes doctrinal and comparative legal methodologies to illuminate the primary regulatory mechanisms governing personal data, restrictions and the individual’s right to access personal information. The conclusions presented herein underscore the challenges inherent in the establishment of a unified approach to personal data in the future. The study underscores that the foundation for effective personal data governance in the digital age is a hybrid approach, integrating flexible legal regulations that readily adapt to technological advancements. The document synthesizes fundamental information and methodologies concerning personal data, which are likely to be of interest to both personal data protection policymakers and legal professionals in general, as well as individuals with non-legal educational backgrounds. The protection of personal information and confidentiality is a matter of concern for each individual.